Human Osteoblast Migration in DC Electrical Fields Depends on Store Operated Ca2+-Release and Is Correlated to Upregulation of Stretch-Activated TRPM7 Channels - Rohde, Marco; Ziebart, Josefin; Kirschstein, Timo; Sellmann, Tina; Porath, Katrin; Kühl, Friederike; Delenda, Bachir; Bahls, Christian; van Rienen, Ursula; Bader, Rainer; Köhling, Rüdiger (Frontiers in Bioengineering and Biotechnology, 2019)
Fracture healing and bone regeneration, particularly in the elderly, remains a challenge. There is an ongoing search for methods to activate osteoblasts, and the application of electrical fields is an attractive approach in this context. Although it is known that such electromagnetic fields lead to osteoblast migration and foster mesenchymal osteogenic differentiation, so far the mechanisms of osteoblast activation remain unclear. Possible mechanisms could rely on increased Ca2+-influx via ion channels, as this is known to activate osteoblasts, e.g. via voltage-sensitive or stretch-sensitive, transient-receptor-potential (TRP) channels. In the present in vitro study, we explored whether electrical fields are able to modulate the expression of voltage-sensitive calcium channels as well as TRP channels in primary human osteoblast cell lines. We show migration speed is significantly increased in stimulated osteoblasts (6.4 ± 2.1 µm/h stimulated, 3.6 ± 1.1 µm/h control), and directed towards the anode. Within a range of 154-445 V/m, field strength did not correlate with migration velocity. Regarding the expression of calcium channels Cav3.2 and Cav1.4, no correlation between electric field and calcium channel expression could be determined. However there was a significant positive correlation between expression of TRPM7 and electric field strength. Electrical stimulation may thus induce TRPM7 expression changes which correlate with cell migration.